1978
DOI: 10.1177/000276427802200103
|View full text |Cite
|
Sign up to set email alerts
|

Social Geography

Abstract: The past fifty years have seen the proliferation of adjectival geographies. During this time human geography became detached from the physical side of the subject, at least to many of its practitioners. Regional geography and settlement geography came to represent markedly different approaches to subject matter as well as distinct spatial scales of study, while historical geography developed as the examination of past geographies. Gradually, various subdividions of human geography also emerged: economic geogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Since the 1950s, West‐based scholars commented on the lack of knowledge on Eastern European cities and socialist cities (see also Ferenčuhová, : 236, referring to the same quotations): Gideon Sjoberg (: 336) considered the scope of research on European cities satisfying, but noted: ‘Less research has been done on present‐day urban centres in eastern and southern Europe'. And in 1978, Eyles and Smith stated:
It is a strange commentary on the spatial selectivity of social geographers in the Anglo‐American tradition that more is known of Chicago than of all state socialist cities put together, or so the literature would suggest (Eyles and Smith, : 54).
…”
Section: Links Between West‐based and Cee Urban Studies During The Stmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the 1950s, West‐based scholars commented on the lack of knowledge on Eastern European cities and socialist cities (see also Ferenčuhová, : 236, referring to the same quotations): Gideon Sjoberg (: 336) considered the scope of research on European cities satisfying, but noted: ‘Less research has been done on present‐day urban centres in eastern and southern Europe'. And in 1978, Eyles and Smith stated:
It is a strange commentary on the spatial selectivity of social geographers in the Anglo‐American tradition that more is known of Chicago than of all state socialist cities put together, or so the literature would suggest (Eyles and Smith, : 54).
…”
Section: Links Between West‐based and Cee Urban Studies During The Stmentioning
confidence: 99%
“…It is a strange commentary on the spatial selectivity of social geographers in the Anglo‐American tradition that more is known of Chicago than of all state socialist cities put together, or so the literature would suggest (Eyles and Smith, : 54).…”
Section: Links Between West‐based and Cee Urban Studies During The Stmentioning
confidence: 99%
“…Indeed, in a recent historical view of the sub-discipline, the author suggested that such movement might possibly result in the demise of social geography (Eyles and Smith 1978). Indeed, in a recent historical view of the sub-discipline, the author suggested that such movement might possibly result in the demise of social geography (Eyles and Smith 1978).…”
mentioning
confidence: 99%